Brecht's Tradition - Spalter, Max (Johns Hopkins University Press, 2019)
Originally published in 1967. Literary scholars often acknowledge that Brecht borrowed from a variety of traditions, including Goethe, Schiller, expressionists, naturalists, and realists, all of whom affected his work. However, they tend not to address any single tradition as exclusively Brecht's. From these various literary traditions, Brecht borrowed formal elements only; compared with other writers to whom he is indebted, Brecht exceeds them in cynicism. They do not convey anything like his pitiless debunking attitude, his corrosive anti-romanticism, his hardheaded refusal to idealize or glorify, and his suspicion of all sentimentalities. This book discusses what the author identifies as the "Brechtian sensibility." Chroniclers of drama have not totally ignored the Brechtian tradition, but too often they are content to note merely that Brecht shared with some writers-particularly Büchner and Wedekind-a proclivity for open drama and episodes of racy realism tinged with poetic feeling. Other critics have not closely studied the various plays of this tradition in order to show how they constitute a distinctive and well-defined species of theater to which Brecht unmistakably belongs.